1972
DOI: 10.1161/01.cir.45.5.1005
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Performance before and after Removal of the Noncontractile Area of the Left Ventricle and Revascularization of the Myocardium

Abstract: The left ventricular volume and the internal surface areas of noncontractile regions were measured by cineangiocardiography at 60 frames/sec in nine patients with a chronic localized noncontractile area of the left ventricle. Arteriosclerotic heart disease was proven in eight patients by means of coronary arteriography. Left ventricular end-diastolic pressure, stroke volume, ejection fraction, mean circumferential shortening, and cardiac output were also measured before and after removal of the noncontractile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…We showed that the extent of the akinetic or dyskinetic segment was closely correlated with left ventricular ejection fraction (r = -0 80, see Fig. 4) and this was consistent with the experience of other authors (Feild et al, 1972;Kitamura et al, 1972;Rogers etal., 1977). Furthermore, it is interesting that the total CK released closely correlated with the ejection fraction, as Rogers et al (1977) have recently reported (anterior infarction: r = -0 71, P < 0 01; inferior infarction: r = -0 73, P < 0-01).…”
Section: Ventricular Functionsupporting
confidence: 92%
“…We showed that the extent of the akinetic or dyskinetic segment was closely correlated with left ventricular ejection fraction (r = -0 80, see Fig. 4) and this was consistent with the experience of other authors (Feild et al, 1972;Kitamura et al, 1972;Rogers etal., 1977). Furthermore, it is interesting that the total CK released closely correlated with the ejection fraction, as Rogers et al (1977) have recently reported (anterior infarction: r = -0 71, P < 0 01; inferior infarction: r = -0 73, P < 0-01).…”
Section: Ventricular Functionsupporting
confidence: 92%
“…The results of aneurysmectomy in our patients are in accord with other studies, namely striking clinical improvement2-5 7 8 17 and reduction of the radiologically estimated heart volume.14 The angiographic finding of a residual aneurysm in 70 per cent of our patients and akinesia in the remainder is also in keeping with the observations of others.4 5 It seems obvious that the area of the suture line with Teflon pledgets will be akinetic, and the presence of a residual aneurysm probably reflects non-excised, more or less fibrotic tissue which is left deliberately as support for sutures. Kitamura et al5 found the excised non-contractile area to be smaller than that estimated in the preoperative angiograms.…”
Section: Discussionsupporting
confidence: 89%
“…Studies comparing ventricular function by cineangiography before and after aneurysmectomy are rare. Kitamura et al (1972) reported a series of 9 patients who underwent aneurysmectomy associated with aortocoronary bypass surgery in 4 patients and internal mammary implants in the remaining 5 patients. The ejection fraction in their series improved from 31 to 44 per cent but remained severely depressed after surgery.…”
Section: Discussionmentioning
confidence: 99%